1990
DOI: 10.1038/bjc.1990.414
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of quercetin on OVCA 433 cells and presence of type II oestrogen binding sites in primary ovarian tumours and cultured cells

Abstract: Summary We investigated the effect of the flavonoid quercetin (Q) on the proliferation of the ovarian cancer cell line OVCA 433. Growth experiments demonstrated that Q exerted a reversible dose-dependent inhibition of cell proliferation in the range of concentrations between 10 nm and 10 M. Two other flavonoids tested, rutin and hesperidin, were ineffective in inhibiting cell growth. Cell cycle analysis showed that the growth inhibitory effect of Q was due to a blocking effect in the GO/GI phase. Using a whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(61 citation statements)
references
References 18 publications
4
54
0
3
Order By: Relevance
“…54 Finally, evidence from in vitro studies of human ovarian cancer cell lines suggests that certain flavonoids can inhibit tumor growth and angiogenesis, interrupt the cell cycle, and induce apoptosis, all of which may be relevant mechanisms for an inverse association between flavonoid intake and ovarian cancer. 20,21,[55][56][57] Although the flavonoid concentrations used in these experimental studies generally exceeded the levels obtainable with typical dietary intake, there was some overlap with the plasma levels of flavonoids observed in feeding studies in humans. For example, the quercetin plasma concentrations observed in several studies where participants ingested 20-100 mg of quercetin, levels comparable with the intakes for women in quintiles 4 and 5 of our study population, were within the range of the quercetin concentrations associated with decreased proliferation of ovarian cancer cells in a study by Scambia et al [57][58][59] This analysis is the largest and most comprehensive assessment of the association between total dietary flavonoid intake and ovarian cancer risk to date.…”
Section: Discussionmentioning
confidence: 99%
“…54 Finally, evidence from in vitro studies of human ovarian cancer cell lines suggests that certain flavonoids can inhibit tumor growth and angiogenesis, interrupt the cell cycle, and induce apoptosis, all of which may be relevant mechanisms for an inverse association between flavonoid intake and ovarian cancer. 20,21,[55][56][57] Although the flavonoid concentrations used in these experimental studies generally exceeded the levels obtainable with typical dietary intake, there was some overlap with the plasma levels of flavonoids observed in feeding studies in humans. For example, the quercetin plasma concentrations observed in several studies where participants ingested 20-100 mg of quercetin, levels comparable with the intakes for women in quintiles 4 and 5 of our study population, were within the range of the quercetin concentrations associated with decreased proliferation of ovarian cancer cells in a study by Scambia et al [57][58][59] This analysis is the largest and most comprehensive assessment of the association between total dietary flavonoid intake and ovarian cancer risk to date.…”
Section: Discussionmentioning
confidence: 99%
“…MeHPLA is an endogenous ligand for nuclear type II sites (14), and occupancy of this site by MeHPLA and bioflavonoids such as luteolin and quercetin appears to inhibit estrogen stimulation of uterine growth in the rat and mammary tumor growth in mice (8,9,14). Subsequent studies demonstrate a direct correlation exists between the occupancy of type II sites by flavonoids such as luteolin, quercetin, and dihydroxybenzylidine acetophenone and the inhibition of breast (8-10), colorectal (11), pancreatic (12, and ovarian cancer (13) as well as the inhibition of leukemia (42) and lymphoblastoid cell proliferation (43). These bioflavonoids do not bind to the ER (8), suggesting that the antiestrogenic and/or inhibitory effects of these compounds on cellular proliferation are mediated through type II sites.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, some investigators have suggested that consumption of weakly estrogenic isoflavonoids such as equol, daidzein, and coumestrol may prevent estrogen-dependent breast and prostate cancers by competing with more active, endogenous estrogens such as estradiol for estrogen receptor (ER) in these target tissues (5)(6)(7). Conversely, studies by our laboratory and others have shown that flavonoids such as luteolin and quercetin bind with high affinity (Kd 1-5 nM) to nuclear type II [3H]estradiol binding sites, but not ER, and this is correlated with the antagonism of estrogenic response in the rat uterus, the inhibition of breast, ovarian, pancreatic, and colon cancer cell proliferation in vitro and estrogen-independent mammary tumor growth in mice (8)(9)(10)(11)(12)(13). Therefore, it is not surprising that a naturally occurring flavonoid metabolite, methyl p-hydroxyphenyllactate (MeHPLA), has been identified as an endogenous cellgrowth-regulating agent and the natural ligand for the type II site (14).…”
mentioning
confidence: 99%
“…It is anti-inflammatory [ 1 ], antithrombotic [2], an tibacterial [3] and antitumoral [4], It has also been reported to prevent gastric mucosal le sions produced by both cold-restraint stress [5] and certain damaging agents such as reser-thermore, the gastric glands were evaluated morphometrically and the involvement of en dogenous prostaglandins in the protective ef fect of quercetin was determined.…”
Section: Introductionmentioning
confidence: 99%